Influences of Environment Context and E-Business Adoption on Business Performance of The Retail Ready-Made Garment Business - Rapeepun Siriwatpatara; Nuttawut Rojniruttikul (My University, 2024)
Purpose: The objective of this research was to study the influences that affect the business performance of the retail ready-made garment businesses. Method: The study focused on the use of a quantitative method with a questionnaire as the tool for data collection from a sample of 240 retail ready-made garment businesses. Data analyses included descriptive statistics and the Structural Equation Model (SEM). Results and Discussions: The findings revealed that the Chi-square = 60.175, df = 44, CMIN/DF = 1.770, GFI=.963, CFI=.992, AGFI=.914, and RMSEA= .055 The structural equation model demonstrated that the environment context and e-business adoption influence the business performance of retail ready-made garment businesses with statistical significance. The variance of the business performance to use was affected by all two factors 74% (R2 = .74) while the remainder was affected by other factors. Nevertheless, it was also revealed that, in the operation of retail ready-made garment businesses, the value chain for e-businesses includes business performance, production, logistics, the infrastructure of human resources, and finance. E-business adoption influences business performance by beneficially leading to efficient operations and the sustainable growth of organizations. Research Implications: Nowadays, the direction of the market and consumers' behavior changes continuously. Naturally, fashion products run in competition with customer demand. At the same time, the duration of sales is starting to shorten due to the faster changing social conditions than in the past. Moreover, the purchasing tendency of customers changes and the product price starts to be lower. However, they focus on buying mix and match garments according to the fashion trend and at a friendly price. Furthermore, the lifestyle of a customer in the new age builds a bond with technology access, such as internet access/ online social via communication devices. These devices are elevated to major roles in modern lifestyles, such as smartphones. It affects alertness in online shopping and greatly influences daily shopping. Entrepreneurs must adjust strategies and business management to be more efficient and effective. Originality/Value: Therefore, the retail ready-made garment business has changed from the past in a high number, in terms of consumption behaviors of target customers, patterns of business administration, and marketing strategy.
Keywords: Business-to-business; Business environment; New business development; Technology Adoption and User Behaviour